MANAJEMEN DAKWAH PERSPEKTIF KH MUSTOFA BISRI - Nasrotu Millatil khusna; Istiqomah Nailul Amani (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
Da’wahl as anl instrument ofl socio religiousl tranformation, playsl a strategicl role inl shaping publicl ethics, thoughtl patterns, andl communal lcharacter. lKH. Ahmadl Mustofa lBisri, al prominent Indonesianl Muslim lscholar, poetl and culturall figure, standsl out asl a centrall figure inl promoting moderatel Islam inl Indonesian. Thisl study aimsl to lidentify, lanalyze, andl contextualize thel methods andl focus ofl KH. Mustofal Bisri da’wahl within thel framework ofl modern, pluralisticl society. Usingl a descriptivel qualitative approachl and literaturel review asl the primaryl technique, thel study revealsl tha lKH. Mustofal Bisri employl a lhumanistic, laesthetic, lcontextual, andl spiritually reflectivel approach tol da’wah. Hisl methods includel dialogical andl empathetic lpreaching, inclusivel aducational lpractices, thel use ofl social lmedia, religiousl literature andl poetry, asl well asl the integrationl of Islamicl values withl artistic lexpression. Thel focus ofl this da’wahl extends beyondl ritual lobservance, emphasizingl religious lconsciouness, interfaithl tolerance, moderatel theology, sociall critique throughl non provocativel language, andl intellectual ampowermentl of thel youth. Hisl soft lspoken, inclusivel communication stylel proves effectivel in promotingl an understandingl of Islaml as al peaceful, lsubstantial, andl humanistic lfaith. Inl conclusion, lKH. Mustofal Bisri da’wahl model offersl a strategicl paradigm forl contemporary Islamicl propagation onel that isl relevant tol the challengesl of thel modern agel and rootedl in thel values ofl peace, justicel and humanl dignity.